Pengaruh Leader Member Exchange (LMX) terhadap Kinerja Karyawan melalui Kepuasan Kerja pada PT. Berlian Jasa Terminal Indonesia - Zulfa, Nuril (Jurnal Ilmu Manajemen, 2021)
This study aims to determine and explain the effect of leader member exchange on employee performance through job satisfaction at PT. Berlian Jasa Terminal Indonesia. This research is a type of causal research with a quantitative approach with a population of 256 permanent employees, and the sampling technique uses probability sampling with a sample of 156 permanent employees. The statistical analysis used in this research is Structural Equation Modeling (SEM) with AMOS 23.0 software. This study indicates that the leader member exchange has a positive and significant effect on job satisfaction because there is a trusting relationship between superiors and subordinates. Job satisfaction has a positive and significant effect on employee performance because it was following company standards. Leader member exchange does not affect employee performance because it structures the performance appraisal. Job satisfaction cannot be an intervening variable between leader member exchange and employee performance due to high workload